The Influence of Entrepreneurial Culture, Domestic Competition, and Trade Openness on Economic Growth: A Semantic Literature Review - Hamdan Hamdan (Universitas Veteran Bangun Nusantara Sukoharjo, 2025)
Objective: This article aims to explore the relationship between entrepreneurial culture, domestic competition, and trade openness, as well as their impact on economic growth. In an increasingly globalized era, understanding the interactions among these factors is crucial for formulating effective policies. Methodology: A semantic literature review was conducted by analyzing 10 relevant articles from various sources, including international journals and academic publications. This process involved data collection through searches in academic databases and bibliometric analysis to identify themes and patterns emerging from previous research. Results: It was found that a strong entrepreneurial culture, healthy domestic competition, and trade openness significantly contribute to economic growth. An entrepreneurial culture that supports innovation and risk-taking creates a conducive environment for the development of new businesses. Additionally, healthy domestic competition enhances efficiency and innovation in the market, while trade openness allows countries to leverage their comparative advantages. Conclusion: This research emphasizes the importance of creating policies that support entrepreneurship and domestic competition, as well as encouraging trade openness to achieve sustainable economic growth. Recommendations for policymakers and stakeholders are presented to assist in formulating effective strategies to support the entrepreneurial ecosystem.